GAMBARAN KEBIASAAN KONSUMSI MAKANAN CEPAT SAJI (FAST FOOD), AKTIVITAS FISIK DAN STATUS GIZI PADA REMAJA DI SMA NEGERI 1 PADANGSIDIMPUAN - Novita Fitriany Akbar Sagala; Fitri Ardiani; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Nutritional problems is one of a public health problems that has not been completely resolved, starting from under weight to the overweight. In the current era of globalization brought many changes including eating pattern such as eating fast food and physical activity.This study aimed looking for the description fast food consumption habits and physical activity with nutritional status on students of SMA Negeri 1 Padangsidimpuan. The design of research used a cross sectional method. The population in this study is all students in SMA Negeri 1 Padangsidimpuan as many as 658 people. with a sample of 87 people. Data obtained using food frequency and 24-hour food recall, physical activity data obtained using the recall activity and nutritional status measured by the BMI for age. Results of research showed that the highest student frequency of nutritional status distribution were fatness and obesity about 48,3%. The average energy intake, protein intake, fat intake, and carbohidrat intake were 30,30%, 28,08%, 49,18%, and 28,61%. Based on the nutritional status of fatness and obesity were 53,1% with mild activity, and there were also a normal nutiritional status were 39,2% with mild activity. Factors relate of nutritional status are fast food consumption habits and physical activity. Suggested to the students who are fatness, it would be better pay attention consumption habits and physical activity such as doing exercise in order to get the ideal weight. Keywords: Fast food, Physical Activity, Nutritional Status